Self-healing in mobile networks with big data - Khatib, Emil Jatib; Barco-Moreno, Raquel; Muñoz, Pablo; De la Bandera Cascales, Isabel; Serrano, Inmaculada (IEEE, 2016)
Mobile networks have rapidly evolved in recent years due to the increase in multimedia traffic and offered services. This has led to a growth in the volume of control data and measurements that are used by self-healing systems. To maintain a certain quality of service, self-healing systems must complete their tasks in a reasonable time. The conjunction of a big volume of data and the limitation of time requires a big data approach to the problem of self-healing. This article reviews the data that self-healing uses as input and justifies its classification as big data. Big data techniques applied to mobile networks are examined, and some use cases along with their big data solutions are surveyed.
Keywords: Sistemas de telecomunicaciones; Comunicación - Análisis de red; Informática móvil; Big data; Mobile communication; Mobile computing; Quality of service; Telecommunication network management